NMR Characterization of Polymethylhydrosiloxane Synthesized using Dichloromethane and Diethyl Ether as Solvent for Vitreous Substitute - Diba Grace Auliya; Vira Fuji Arini; Fitrilawati Fitrilawati; Lusi Safriani; Risdiana Risdiana; Nabillah Fa'diyyah Zahra (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2023)
Polymethylhydrosiloxane (PMHS) can be synthesized from dichloromethylsilane (DCHS) by the hydrolysis-condensation method. In this synthesis method, a solvent is needed. Dichloromethane (DCM) or diethyl ether (DE) can be used as a solvent in the synthesis of PMHS. These two solvents greatly affect the physical properties of the resulting PMHS. Therefore, studies are needed to look at the characteristics and chemical content of the PMHS synthesized using these two solvents. In this research, we reported the characteristics and content studies of PMHS synthesized using different solvents, DCM and DE, using 1H-NMR and 13C-NMR. It was found that both samples had three peaks (Si-H, Si-CH3, and Si-CH3) on 1H-NMR measurement and one peak (Si-CH3) on 13C-NMR measurement. All of the peaks found were by the characteristics of PMHS and no other elements were found from solvents indicating that the PMHS samples had been successfully synthesized with a high degree of purity. In addition, the possibility of structures formed in the PMHS samples was also obtained.